Ketone monoester attenuates declines in cognitive performance and oxygen saturation during acute severe hypoxic exposure under resting conditions - McClure, T. S.; Phillips, J.; Koutnik, A. P.; Coleman, K.; Chappe, E.; Cutter, G. R.; Egan, B.; Norell, T.; Stubbs, B. J.; Bamman, M. M.; Kernagis, D. (Experimental Physiology, 2024)
Exogenous ketone supplements are a potential augmentation strategy for cognitive resilience during acute hypoxic exposure due to their capacity to attenuate the decline in oxygen (O2) availability, and by providing an alternative substrate for cerebral metabolism. Utilizing a single-blind randomized crossover design, 16 male military personnel (age, 25.3 ± 2.4 year, body mass, 86.2 ± 9.3 kg) performed tests of cognitive performance at rest in three environments: room air (baseline), normoxia (20 min; 0 m; 20.9% O2) and hypoxia (20 min; 6096 m, 9.7% O2) using a reduced O2 breathing device (ROBD). (R)-3-Hydroxybutyl (R)-3-hydroxybutyrate (R-BD R-ßHB) ketone monoester (KME; 650 mg/kg, split dose given at 30 min prior to each exposure) or taste-matched placebo (PLA) was ingested prior to normoxia and hypoxic exposure. Blood R-ßHB and glucose concentrations, cognitive performance and O2 saturation (SpO2) were collected throughout. KME ingestion increased blood R-ßHB concentration, which was rapid and sustained (>4 mM 30 min post; P < 0.001) and accompanied by lower blood glucose concentration (~20 mg/dL; P < 0.01) compared to PLA. Declines in cognitive performance during hypoxic exposure, assessed as cognitive efficiency during a Defense Automated Neurobehavioral Assessment (DANA) code substitution task, were attenuated with KME leading to 6.8 (95% CL: 1.0, 12.6) more correct responses per minute compared to PLA (P = 0.018). The decline in SpO2 during hypoxic exposure was attenuated (6.40% SpO2; 95% CL: 0.04, 12.75; P = 0.049) in KME compared to PLA (KME, 76.8 ± 6.4% SpO2; PLA, 70.4 ± 7.4% SpO2). Acute ingestion of KME attenuated the decline in cognitive performance during acute severe hypoxic exposure, which coincided with attenuation of declines in O2 saturation.